2013
DOI: 10.1007/s40098-013-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Load Attenuation Using EPS Geofoam Buffers in Rigid Wall Applications

Abstract: The paper is a synthesis of previously published work by the authors that is focused on the use of EPS geofoam buffers for seismic load attenuation against rigid basement and soil retaining walls. The paper begins with a brief description of the first documented field application followed by a description of physical 1 m-high reduced-scale shaking table tests that provided the first "proof of concept". Next, details of the development and verification of a displacement-based model and a FLAC numerical model ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…This leads to the expression for the diameter-thickness ratio (DT). This expression is also used when describing the motion of microscopic particles [15,16]:…”
Section: Definition Of Diameter-thickness Ratio and Height-thickness ...mentioning
confidence: 99%
“…This leads to the expression for the diameter-thickness ratio (DT). This expression is also used when describing the motion of microscopic particles [15,16]:…”
Section: Definition Of Diameter-thickness Ratio and Height-thickness ...mentioning
confidence: 99%
“…In addition, EPS beads are of low density and high compressibility. They are often used as filling materials in earthquake buffers, such as backfilling materials for retaining walls, and filling materials for trenches [21,22,23,24]. These lightweight filling materials can be used as a buffer layer to reduce the dynamic earth loads for the seismic effect of rigid basements and retaining walls.…”
Section: Introductionmentioning
confidence: 99%
“…These lightweight filling materials can be used as a buffer layer to reduce the dynamic earth loads for the seismic effect of rigid basements and retaining walls. Bathurst and Zarnani [23] and Gao et al [25] conducted a series of shaking table tests to study the seismic performance of the EPS block geofoams. They found that the EPS can effectively reduce the seismic load and the lateral thrust increment of the rigid basement and retaining wall.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue of the Indian Geotechnical Journal contains contributions on several practical aspects and areas of Geosynthetic engineering, namely retaining structure/wall [1,2], soil-geosynthetic/geosynthetic-geosynthetic interaction [3,4], foundation [5], embankment [6], slope [7], landfill [8], and erosion control [9,10]. I do hope the researchers and the engineers may find these contributions very useful.…”
mentioning
confidence: 99%
“…The first paper by Bathurst and Zarnani [1] is a synthesis of the previous work carried out by the authors on the use of expanded polystyrene (EPS) geofoam buffers for the seismic load attenuation against rigid basement and soil retaining walls. The major practical outcome of their research is the identification of buffer stiffness as the parameter of interest to design these systems.…”
mentioning
confidence: 99%